Respostas

2014-04-15T22:01:52-03:00
A) y=2(3)+1=6+1=7
y=2(-3)+1=6+1=7


2014-04-15T22:27:23-03:00
Pontos A(3,7) e B(-3,-5)

a) y = 2x+1    b) y = 2x – 1     c) y = x – 1     d) f(x) = x +

A(3,7)                                                B(-3,-5)
a) y = 2x+1                                     a) y= 2x + 1

y= 2(3) + 1                                          y=2(-3) + 1
y= 6 + 1                                               y= - 6 + 1
y= 7                                                     y= -5 
  

  b) y = 2x – 1                                   b) y= 2x - 1
     y= 2(3) - 1                                       y =2(-3) - 1
    y= 6 - 1                                            y = - 6 - 1
    y= 5                                                  y= - 7


c) y = x – 1                                        c) y = x - 1
   y = 3 - 1                                              y= - 3 - 1
   y= 2                                                    y= - 4

d) f(x) = x +
f(x) = y
então
y = x +


RESPOSTA   até agora é a letra (a)
a) y= 2x + 1     é a função que passa pelos pontos: A(3,7) e B(-3,-5)